Characterization of Commercial Non-Alcoholic Beers in Two Locations, Finland and China - Kelanne, Niina; Zhu, Yuxuan; Rysä, Tuomas; Yang, Baoru; Zhu Baoqing; Laaksonen, Oskar (MDPI, 2025)
Consumption of non-alcoholic beer (NAB) is continuously increasing in many countries. NABs are produced with varying technologies, resulting in different sensory properties. Previous studies have focused on understanding the consumers’ acceptance and preferences among different types of NAB. However, few studies have focused on the sensory characterization of commercial NABs produced with different methods. This study aimed to find key sensory characteristics in lager, Indian pale ale, and pilsner-type NABs with untrained panels by conducting tests in Finland and China. Participants were asked to Check-All-That-Apply for odors and Rate-All-That-Apply for flavors. Additionally, hedonic responses to odor and flavor pleasantness were rated. Chinese participants used more different and more often-used attributes to describe NABs. More varying descriptors were used on the NAB samples chosen as the most pleasant ones, indicating more complex sensory properties. Participants from both locations preferred lager-type beers characterized as ‘fresh’ odor and ‘fruity’, ‘floral’, and ‘sweet’ flavors and less frequently found Indian-pale-ale-type NABs pleasant, describing them as ‘sour’, ‘bitter’, ‘fermented’, and ‘pungent’ flavors. The flavor pleasantness correlated more with the samples frequently chosen as the most pleasant than odor pleasantness. No clear connection was found between the production method of NAB and consumers’ acceptance, demonstrating that all production methods can be used to produce non-alcoholic beers with sensory properties acceptable to consumers.